Revolusi hijau dalam pendidikan kristiani: Menghidupkan ecophilia dalam spiritualitas keseharian - Sihombing, Elsina; Sianturi, Julius; Simamora, Lince (KURIOS, 2024)
Christian religious education in Indonesia must integrate the concept of ecophilia (love for the environment) to overcome the increasingly severe environmental crisis. This research aims to develop strategies for implementing ecophilia in Christian education and evaluating its impact on student attitudes and behavior, as well as collaboration throughout the school community in environmentally friendly practices. Using a qualitative approach with thematic analysis, this research found that integrating ecophilia in the curriculum and school activities increased ecological awareness and the formation of students' character who care about the en-vironment. Through active participation in environmental programs, the school community becomes an effective agent of change, reflecting faith manifested in concrete actions. The results of this research provide a concrete framework for integrating ecological responsibility into daily spi-rituality in Christian religious education, creating an ecologically and spiritually responsible generation. Through this approach, Christian schools can become a model for other communities in implementing ecophilia and strengthening daily spirituality through concrete actions that reflect love and concern for the environment.   Abstrak Pendidikan agama Kristen di Indonesia harus mengintegrasikan konsep ecophilia (cinta kasih terhadap alam) untuk mengatasi krisis lingkungan yang semakin parah. Penelitian ini bertujuan mengembang-kan strategi implementasi ecophilia dalam pendidikan kristiani dan meng-evaluasi dampaknya terhadap sikap dan perilaku siswa, serta kolaborasi seluruh komunitas sekolah dalam praktik ramah lingkungan. Dengan menggunakan pendekatan kualitatif melalui analisis tematik, penelitian ini menemukan bahwa integrasi ecophilia dalam kurikulum dan aktivitas sekolah menunjukkan peningkatan kesadaran ekologis dan pembentukan karakter siswa yang peduli lingkungan. Komunitas sekolah, melalui par-tisipasi aktif dalam program lingkungan, menjadi agen perubahan yang efektif, mencerminkan iman yang terwujud dalam tindakan nyata. Hasil penelitian ini memberikan kerangka kerja konkret untuk mengintegrasi-kan tanggung jawab ekologis ke dalam spiritualitas keseharian dalam pen-didikan agama Kristen, menciptakan generasi yang bertanggung jawab secara ekologis dan spiritual. Melalui pendekatan ini, sekolah Kristen dapat menjadi model bagi komunitas lainnya dalam menerapkan ecophilia dan memperkuat spiritualitas sehari-hari melalui tindakan nyata yang mencerminkan kasih dan kepedulian terhadap lingkungan.